Putting transformative learning in higher education based on linking capital - Syaharuddin Syaharuddin; Mutiani Mutiani; Muhammad Rezky Noor Handy; Ersis Warmansyah Abbas; Jumriani Jumriani (Journal of Education and Learning (EduLearn), 2022)
This study aimed to analyze learning at the level of higher education. The practice of higher education, of course, also requires a transformation of learning. It is intended to achieve the competencies needed in the 21st century.The study used a qualitative approach. Observations were made on online learning practices at Lambung Mangkurat University, Banjarmasin, Indonesia from March to May 2021. In-depth interviews employed with 17 students who live in Banjarmasin. Miles and Huberman's data analysis technique reduces interview data. The study results described that learning at the higher education level has differences in the achievement of the graduate profile. There are two main patterns, namely, institution-centered learning and student-centered learning. The student's need for network strengthening requires the systemic transformation of learning. One learning transformation that can be carried out is strengthening learning practices outside the classroom with partners (stakeholders). The primary purpose of partner involvement is a condition designed so that students can increase network capital. This linking capital is expected to be an opportunity for students to increase student succession when they graduate from higher education.